2001
DOI: 10.1046/j.0306-5251.2001.01405.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal differences in finger skin temperature and microvascular blood flow in healthy men and women are exaggerated in women with primary Raynaud's phenomenon

Abstract: Aims Patients with primary Raynaud's phenomenon (PRP) have more severe symptoms in the winter. The aetiology of this is more complex than simply increased vasoconstriction in response to the immediate ambient temperature. The aim of this study was to investigate differences in skin temperature (Tsk), microvascular blood ow and responses to endothelium-dependent and independent vasodilators in healthy controls, and women with PRP under identical environmental temperatures but in different seasons. Methods Ten w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 25 publications
2
25
0
1
Order By: Relevance
“…The second limitation of our study is the influence of ambient temperature on the severity of RP (29,30). Ambient temperature variability during the study period affects all trials of therapy for RP.…”
Section: Discussionmentioning
confidence: 98%
“…The second limitation of our study is the influence of ambient temperature on the severity of RP (29,30). Ambient temperature variability during the study period affects all trials of therapy for RP.…”
Section: Discussionmentioning
confidence: 98%
“…In general, skin temperature and red blood cell fl ux assessed after acclimatization were consistently lower in winter than in summer. Seasonal variations were more pronounced in women than in men [35] . Men had the warmest fi ngers on arrival, and women needed less cooling to achieve the same skin temperature as men at 15 ° C. Various seasonal effects were observed in a timecourse study performed on 22 presumably Japanese subjects, using the neck of 11 males and the ventral forearm of 11 females as the test areas [36] .…”
Section: Circaannual/seasonal Rhythmsmentioning
confidence: 91%
“…In a small scale study, seasonal differences in fi nger skin temperature were assessed [35] . Skin temperature was assessed after arrival, after acclimatization and after decreasing (15 ° C) or increasing (35 ° C) the ambient temperature.…”
Section: Circaannual/seasonal Rhythmsmentioning
confidence: 99%
“…Cold stimuli would cause vasoconstriction and deteriorate limb ischemia. Indeed, a few previous studies reported that a cold environment more severely impairs the peripheral microvascular blood flow 14,15) . However, there remain questions regarding the influence of cold temperatures on the peripheral macrovascular blood flow 16) .…”
Section: Discussionmentioning
confidence: 99%